Isolation of AntiBiotic Resistant Bacteria From The Handphones of Male and Female Users in INTI International University - Lithiya, Letchumy Thiagu (2017)
The current most indispensable accessories of humans is the mobile phone. Despite their vast benefits, mobile phones are undoubtly a good reservoir for bacterial transmission due to its heavy usage. This makes mobile phones excellent tools to transmit bacteria including antibiotic resistant bacteria. Thus, the objectives of this study were to isolate antibiotic-resistant bacteria from the mobile phones of male and female users in INTI International University and to preliminarily compare the pattern of distribution of antibiotic-resistant bacteria between the gender using the chi square test. Twenty-six touch screen mobile phones samples were collected from the students and lecturers of INTI International University by rubbing the screens aseptically using sterile cotton swabs. The samples were cultured onto nutrient agar to obtain pure cultures. All the isolates were subjected to confirmatory tests as well as the antibiotic susceptibility test. The antibiotic susceptibility was determined using the Clinical and Laboratory Standards Institute, 2017. A total of 53 pure culture isolates were obtained from the touch screen mobile phones, where, 48 isolates were gram-positive and the remaining 5 were gram-negative bacteria. The genera of the isolates were predicted based on the results obtained from the confirmatory tests and were confirmed with the Bergey’s manual. According to the results, the possible genera of the isolates that had been isolated from the touch screen mobile phone samples were Enterobacter sp, Staphylococcus epidermidis, Staphylococcus aureus, Micrococcus sp, Propionibacterium sp and Bacillus licheniformis. Out of the 48 gram-positive, 24 isolates were resistant to at least one type of antibiotics. Apart from that, 14 isolates were resistant to cefoxitin, 18 were susceptible but the susceptibility of the other 16 isolates could not be determined. However, all the gram-negative bacteria were susceptible to all three antibiotics, namely, tetracycline, amikacin and erythromycin. The chi square tests indicated that there are no significant differences in the number of antibiotic-resistant bacteria isolated from male and female users but this can be better determined from a larger sample size.